Interactive methods in teaching visual arts - Amanova Gulchexra Xamzayevna (Peerian Journals Publishing, 2024)
In the following sections of this article, we will delve deeper into the various interactive methods used in teaching visual arts, explore their advantages and practical applications in the classroom. From hands-on activities that encourage experimentation in visual arts education to technology integration that opens up new artistic possibilities, interactive teaching methods are rich in learning that fosters creativity, curiosity, and a lifelong passion for the arts and offers a dynamic approach.
Keywords: Education; visual arts; interactive methods; blackboard